Assessment of rural tourism for social, environmental, and customer sustainability in a multi-ethnic community of Gandaki Province, Nepal - Tiwari, Surendra; Thi, Phuoc Lai Nguyen; Ahmad, Mokbul Morshed; Shrestha, Rajendra Prasad; AIT Scholarship; Strengthening Groundwater Governance in Rapidly Urbanizing Areas of the Lower Mekong Region Project (Pathum Thani : Asian Institute of Technology, 2024)
Rural tourism is a rapidly growing sector aimed at preserving the local environment and culture while boosting rural communities{u2019} economic well-being. However, its uncontrolled growth poses social and environmental challenges, threatening sustainability in rural areas. Using the DPSIR (Drivers, Pressure, State, Impact, Response) framework, this study sought to assess whether rural tourism development promotes social, environmental, and customer sustainability in a multi-ethnic community along the Annapurna Sanctuary Trail (AST), Gandaki Province, Nepal. Using mixed methods with sequential explanatory techniques, the study assessed the socio-cultural, economic, and environmental impacts of rural tourism through data from 120 face-to-face household surveys. The study also analysed customer (tourists) sustainability based on data from 100 visitors to the AST, focusing on attribute and behavioural factors.Key drivers of rural tourism along the AST include abundant natural and cultural resources, growing demand for rural tourism activities, and supportive government policies promoting ecotourism and homestay. These drivers imposed environmental pressures such as over-exploitation of resources and pollution while contributing to social equity and economic empowerment, especially among marginalised groups like women, Dalits, and Janajatis. Furthermore, locals from multi-ethnic backgrounds benefitted through employment opportunities, selling local products, leasing land, and improved social services. However, overreliance on tourism has caused abandonment of agriculture, loss of traditional agricultural practices, and food insecurity. Raising living costs and income inequality have pushed economically disadvantaged communities to migrate. Moreover, the mass influx of tourists also increased waste accumulation along the trails, posing environmental hazards and public health concerns.To enhance the social, environmental, and customer (tourist) sustainability in multi ethnic rural communities, the study recommends regulating local prices, employing economically deprived locals, integrating agricultural knowledge into tourism, preserving local culture, and improving circular waste management behaviours.Further research should include non-tourism-based households to capture diverse community perspectives and conduct qualitative research to explore additional factors affecting the sustainability of multi-ethnic communities in rural tourism contexts.
A dissertation submitted in patial fulfillment of the requirements for the Degree of Doctor of Philosophy in Development Planning Management and Innovation
Thesis (Ph.D.) - Asian Institute of Technology, 2024
Keywords: Rural tourism -- Nepal -- Gandaki; Sustainable tourism -- Nepal -- Gandaki